Interactive Art Readings Focusing on Gilles Deleuze’s Thoughts - Sara Jahangiri; Hossein Ardalani (Journal of Visual Art and Design, 2022)
Gilles Deleuze is a post-structuralist philosopher whose viewpoints have a postmodern and post-structuralist atmosphere that transform any solid and stable structure into dynamism, oppression and fluidity. In the twentieth century, several developments occurred in the arts and technology. This brought about the emergence of new art forms, including interactive art. In this research, we deal with interactive art from the viewpoint of Deleuze based on the interpretation of two examples of works of an interactive artist, i.e., Maurice Benayoun. We looked specifically at the role of the audience in this art form. The research methodology used was descriptive-analytical and the method of information analysis was qualitative. The results of this study show that in interactive art, in as in Deleuze’s view, stagnation and one-dimensionality do not make sense. The audience finds himself/herself in between the work and the personal. However, the meaning of the artwork and its transmission among the creator, the work, and the audience is always in progress, a fluid flow happening in the middle of the potential and actual task.